SCREENING PENANDA MIKROSATELIT Shorea curtisii TERHADAP JENIS-JENIS SHOREA PENGHASIL TENGKAWANG - ILG Nurtjahjaningsih; AYPBC Widyatmoko; Purnamila Sulistyawati; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2012)
Screening primer is an effective method to develop microsatellite markers from related taxa. Aim of this study was to develop microsatellite markers of four Shorea producing tengkawang oil, i.e. Shorea gysbertiana, Shorea macrophylla, Shorea pinanga and Shorea stenoptera by screening microsatellite primers of Shorea curtisii. Leaf samples of the four Shorea were collected from nursery at Center for Forest Biotechnology and Tree Improvement Research in Yogyakarta. Four microsatellite primers of S. curtisii i.e. Shc-1, Shc-2, Shc-7 and Shc-9 had been used to screen. Results showed that numerous alleles were shared among the Shorea. The expected heterozygosity (HE) for locus Shc-1 ranged between 0.594 and 0.722; locus Shc-2 ranged between 0.219 and 0.611; locus Shc-7 ranged between 0.594 and 0.778; and locus Shc-9 ranged between 0.594 and 0.844. Coefficient of inbreeding (FIS) value was low and it was insignificant deviated from Hardy-Weinberg Equilibrium (HWE) at  almost all loci except Shc-1 of S.  pinanga. A dendrogram showed two clusters; S. gysbertsiana and S. macrophylla represented in one cluster, while S. pinanga and S. stenoptera represented in another cluster. Therefore the developed microsatellite markers are possible to be applied for studying population genetics and mating system of these species.